Use of static and dynamic in vitro models to simulate Prato cheese gastrointestinal digestion: Effect of Lactobacillus helveticus LH-B02 addition on peptides bioaccessibility - Baptista, Débora Parra; Salgaço, Mateus Kawata [UNESP]; Sivieri, Katia [UNESP]; Gigante, Mirna Lúcia (Elsevier, 2020)
The use of adjunct proteolytic cultures in the manufacture of ripened cheese is a strategy used to favor the release of bioactive peptides during ripening. However, the presence of these peptides in cheese does not guarantee their biological activity since the bioactivity depends on the stability of these compounds during gastrointestinal digestion. This study aimed to evaluate the effect of the gastrointestinal digestion on the peptide profile of Prato cheeses produced with and without the addition of Lactobacillus helveticus LH-B02 as an adjunct culture, using in vitro static and dynamic models to simulate the digestion. In both models studied, proteolysis during the simulation of gastrointestinal digestion resulted in an approximation of the peptide profile of the cheeses. Simulated digestion led to both the hydrolysis of bioactive peptides detected in the cheeses and the release of a new bioactive fragment.
Keywords: Adjunct culture; Bioactive peptides; Casein; Digestion; Proteolysis